Momentum spectroscopy for multiple ionization of cold rubidium in the elliptically polarized laser field - Yuan, Junyang; Ma, Yixuan; Li, Renyuan; Ma, Huanyu; Zhang, Yizhu; Ye, Difa; Shen, Zhenjie; Yan, Tianmin; Wang, Xincheng; Weidemüller, Matthias; Jiang, Yuhai (Chinese physics letters, 2020)
Employing recently developed magneto-optical trap recoil ion momentum spectroscopy (MOTRIMS) combined with cold atoms, strong laser pulse, and ultrafast technologies, we study momentum distributions of the multiply ionized cold rubidium (Rb) induced by the elliptically polarized laser pulses (35 fs, 1.3 × 1015 W/cm2). The complete vector momenta of Rb n+ ions up to charge state n = 4 are recorded with extremely high resolution (0.12 a.u. for Rb+). Variations of characteristic multi-bands are displayed in momentum distributions because the ellipticity varies from the linear to circular polarization, are interpreted qualitatively with the classical over-barrier ionization model. Present momentum spectroscopy of cold heavy alkali atoms presents novel strong-field phenomena beyond the noble gases.
Gesehen am 24.09.2020